Calcium handling and atrial fibrillation - Heijman, Jordi; Voigt, Niels; Dobrev, Dobromir (Wiener medizinische Wochenschrift, 2012)
Summary: Atrial fibrillation (AF) is the most prevalent sustained cardiac arrhythmia in the clinical setting. It is associated with substantial cardiovascular morbidity and mortality. Recent research has indicated that abnormal Ca2+ handling plays a critical role in the induction and maintenance of AF, contributing to ectopic activity, AF-maintaining reentry circuits and related prothrombotic atrial hypocontractility. The AF-specific Ca2+-handling abnormalities may constitute viable therapeutic approaches to treat AF. Here, we review the causes, consequences, and therapeutic implications of altered atrial Ca2+ handling for AF pathophysiology.